The Effect of Minimum Equity Requirements on the Profitability oof General Insurance Companies in Indonesia - Siti Ayu Setia Nastiti; Lenny Suardi (Green Publisher Indonesia, 2026)
Indonesia’s general insurance industry plays an important role in maintaining financial system stability and providing protection against various financial risks. However, the introduction of Financial Services Authority Regulation (POJK) No. 23 of 2023, which increases minimum equity requirements, has created challenges for insurers, particularly regarding capital adequacy and profitability. This study aims to examine the effect of minimum equity requirements on the profitability and equity structure of general insurance companies in Indonesia. A quantitative approach was employed using panel data regression based on secondary data obtained from OJK Insurance Statistics and companies’ annual financial statements for 2021–2025. The sample comprised 67 general insurance companies, resulting in 335 observations. The results indicate that the implementation of POJK No. 23 of 2023 significantly increased insurers’ total equity, suggesting that the regulation encouraged companies to strengthen their capital structures. The regulation also demonstrated a positive effect on profitability, particularly Return on Equity (ROE), while its effect on Return on Assets (ROA) was comparatively weaker. However, compliance with the minimum equity threshold itself did not significantly affect either ROA or ROE. In conclusion, POJK No. 23 of 2023 is more effective in strengthening capital resilience and financial stability than in directly enhancing profitability among compliant general insurance companies.